Risk Management Study in Smart City Development: Challenges and Opportunities in Bali - Sanjaya, I Putu Ari; Sudarsana, Dewa Ketut; Yana, Anak Agung Gde Agung; Dewi, Anak Agung Diah Parami; Dwijendra, Ngakan Ketut Acwin (Universitas Ibn Khaldun Bogor, 2025)
The development of smart cities in Bali is a significant initiative aimed at enhancing the quality of life for residents through the application of advanced information and communication technology (ICT). As a prominent tourism destination, Bali faces unique challenges in integrating modern technology with its cultural heritage and natural environment. Effective project risk management is crucial in mitigating potential failures and ensuring the success of these complex and high-investment smart city projects. This study examines the challenges and opportunities in implementing risk management for smart city development in Bali. The research employs a mixed-methods approach, combining qualitative and quantitative data collection and analysis. Primary data were gathered through in-depth interviews with key stakeholders, including local government officials, project developers, and community members. Secondary data were obtained from relevant literature, project reports, and policy documents. The findings identify key technical, non-technical, and environmental risks that may impede the success of smart city projects. Technical risks include technology failures and design errors, while non-technical risks involve regulatory changes and community resistance. Environmental risks pertain to the negative impacts on the local ecosystem. The study reveals that these risks significantly affect the critical dimensions of smart city development, such as economic, social, and environmental aspects. To address these challenges, the research proposes several mitigation strategies, including enhancing technical capacity, regulatory socialization, and community engagement in the planning and implementation processes. The developed risk management model offers practical insights for policymakers, project developers, and stakeholders in managing risks and leveraging opportunities to ensure the successful development of smart cities in Bali. This study contributes to the literature by providing a comprehensive analysis of the unique context of Bali, highlighting the importance of an effective risk management framework tailored to local conditions. The findings and recommendations serve as a practical guide for improving the resilience and sustainability of smart city projects, ultimately benefiting the broader community.